2012
DOI: 10.1155/2012/720201
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Intracorneal Graphite Deposits following Graphite Pencil Injury

Abstract: Reports of graphite pencil lead injuries to the eye are rare. Although graphite is considered to remain inert in the eye, it has been known to cause severe inflammation and damage to ocular structures. We report a case of a 12-year-old girl with intracorneal graphite foreign bodies following a graphite pencil injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…There have been few reports of ocular graphite deposition in the literature [ 2 , 5 , 7 9 ]. Hamanaka et al reported an 8-year-old boy who presented with an intraocular foreign body composed of graphite pencil lead.…”
Section: Discussionmentioning
confidence: 99%
“…There have been few reports of ocular graphite deposition in the literature [ 2 , 5 , 7 9 ]. Hamanaka et al reported an 8-year-old boy who presented with an intraocular foreign body composed of graphite pencil lead.…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrated that carbon particles in the corneal stroma were well tolerated in the long term. Philip et al 3 reported a case in which intracorneal carbon particles were observed during routine eye examination in a patient who had sustained a pencil injury to the same eye 3 years earlier. Slit-lamp examination of the right eye revealed anterior stromal scar, though no signs of previous or current inflammation were detected in the intraocular structures.…”
Section: Discussionmentioning
confidence: 99%
“… 1 There are few cases in the literature of intracorneal carbon particles 2 , 3 and intraocular penetrating injuries 4 , 5 , 6 , 7 , 8 due to pencil lead. Although it has been reported that the carbon particles from pencil lead may remain dormant in the eye without inducing inflammation for long periods of time, 2 , 3 they have also been reported to cause severe endophthalmitis5 or endothelial dysfunction and corneal edema. 6 In this report we share three cases of pencil lead injury, one with corneal stromal injury and two with intraocular penetrating injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Pencil injuries to the eye and adnexal tissues have variable presentations within the few reported cases [1,2,3,4,5,6]. In the skin, pencil “lead” injuries may present anytime between 1.5 and 58 years after implantation of the core [7,8,9].…”
Section: Introductionmentioning
confidence: 99%